Relevansi Ekonomi Mikro Islam dalam Perspektif Batasan Teori dan Pemikiran Ekonomi Muslim Klasik - Albasri, Bahrul Anam; Rifaldi, Aivan; Munajim, Ahmad (Indonesian Journal of Research and Service Studies, 2024)
This study employs a qualitative research design using a library research approach to examine Islamic microeconomics, focusing on its urgency, theoretical boundaries, and the contributions of classical Muslim economic thought. Data are derived from primary sources, including classical works of prominent Muslim scholars such as Al-Ghazali, Ibn Taymiyyah, and Ibn Khaldun, as well as secondary sources like academic books and journal articles. The data collection technique involves systematic documentation, classification, and critical reading of relevant literature. Data analysis is conducted through descriptive qualitative methods, including data reduction, categorization, interpretation, and conclusion drawing. The study applies historical, conceptual, and comparative approaches to explore the evolution and distinct characteristics of Islamic microeconomic theory. The findings highlight the relevance of Islamic microeconomics in addressing contemporary economic issues, its normative limitations based on Sharia principles, and the significant intellectual contributions of classical Muslim scholars to economic thought.